Losing on the Home Front? Battlefield Casualties, Media, and Public Support for Foreign Interventions - Thiemo Fetzer; Pedro C. L. Souza; Oliver Vanden Eynde; Austin L. Wright (Center for Economic Studies and ifo Institute (CESifo), 2023)
How domestic constituents respond to signals of weakness in foreign wars remains an important question in international relations. In this paper, we study the impact of battlefield casualties and media coverage on public demand for war termination. To identify the effect of troop fatalities, we leverage the otherwise exogenous timing of survey collection across 26,776 respondents from nine members of the International Security Assistance Force (ISAF) in Afghanistan. Quasi-experimental evidence demonstrates that battlefield casualties increase coverage of the Afghan conflict and public demand for withdrawal, with heterogeneous effects consistent with an original theoretical argument. Evidence from a survey experiment replicates the main results. To shed light on the media mechanism, we leverage a news pressure design and find that major sporting matches occurring around the time of battlefield casualties drive down subsequent coverage, and significantly weaken the effect of casualties on support for war termination. These results highlight the crucial role that media play in shaping public support for foreign military interventions.
Keywords: 330; international security; public opinion; political economy; Afghanistan; NATO